A qualitative investigation of the perceived role of peers in influencing substance use among youth in Monrovia, Liberia. Issue 4 (2nd October 2018) - Lange, Brittany C. L.; Pullen, Samuel J.; Petruzzi, Liana J.; Parnarouskis, Lindsey; Dominguez, Silvia; Harris, Benjamin; Quiterio, Nicole; Fernandez, Pedro J.; Lekpeh, Gondah; Slopadoe, Siede P.; Henderson, David C.; Borba, Christina P.C.
ABSTRACT: Substance use and abuse has become an issue for adolescents globally. While multiple factors contribute to substance use, peer influence is particularly important. As such, this study aimed to examine students' beliefs related to substance use, including the role peers have on substance use behaviors in Monrovia, Liberia. Nine focus groups were conducted with a total of 72 public school students in Monrovia. All focus groups were recorded, transcribed verbatim, and analyzed by a team of trained, qualitative coders. Per student report, peers both directly and indirectly influenced decisions related to substance use. Direct influence from peers included peer pressure, bullying and taunts, and putting drugs or alcohol into food and drinks to be consumed by peers without their knowledge. Indirect influence occurred when peers witnessed the substance use behaviors of others. Despite this, there was a subset of individuals who refused peer pressure, citing a number of reasons, including future negative outcomes. Given the central role that peers play in the substance use behaviors of adolescents in the Liberian cultural context, public health policies and interventions should target these interactions.